Peran Suami Dalam Memberikan Dukungan Persalinan - Kristianingrum, Dhita Yuniar (Program Studi S1 Kebidanan - Fakultas Sains dan Kesehatan Universitas PGRI Adi Buana Surabaya, 2021)
In Indonesia, the maternal mortality rate reaches 830 per day due to several problems during pregnancy and childbirth. The causes of problems vary both physiological and psychological. Psychological affects the mother's mental anxiety. Here the husband's role is very important. The husband's role will have an effect on the wife's emotions, if the wife feels calm, the central nerve cells produce the hormone oxytocin properly. The purpose of the study was to determine the role of the husband in providing childbirth support to postpartum mothers at the Jabon Jombang Health Center.The design of this study uses Descriptive, with a population of 32 respondents taken by Total Sampling, namely all husbands who have postpartum mothers at Jabon Jombang Health Center on July 24-27 2017. In collecting research data using questionnaires, then processed with Editing, Coding, Scoring, Tabulating, and Percentage.The results of the study were obtained from 32 respondents, that almost all respondents played an active role of 12 respondents (37.5%), and respondents who played a passive role were 20 respondents (62.5%). Based on the results of the study it can be concluded that there are still many husbands who play a passive role in preparing for their wife's needs during childbirth at Jabon Jombang Health Center